Lead and cadmium in seabirds of South Africa - Summers, Carly (Clemson University Libraries, 2012)
Levels of lead (Pb) and cadmium (Cd) were investigated as potential stressors in adult African penguins (Spheniscus demersus) in the Western Cape Province, South Africa and in nine species of breeding seabirds on Marion Island, South Africa. Seabirds are sentinels of environmental pollution and allow researchers to study contaminant dynamics in marine ecosystems. Many seabirds occupy high trophic positions, which gives them the potential to highlight threats to other apex predators from environmental pollutants. They also accumulate contaminants in higher concentrations because of their greater size and lifespan than may be detectable in lower trophic organisms. Blood samples were collected from African penguins between 2007 and 2011, and from nine species of seabirds on Marion Island in 2011. The whole blood method for graphite furnace atomic absorption spectroscopy was used to analyze samples. In penguins, the majority of blood Pb levels (97%) and blood Cd levels (80%) were within levels considered to be background exposure. Significant differences were observed among colonies, years, and seasons. The Pearson correlation coefficient between Pb and Cd for individual penguins was 0.3149 (p = 0.0005). Marion Island samples revealed individual blood Pb concentrations ranged from 0.80 (king penguin Aptenodytes patagonicus) to 54.89 μg/dL (wandering albatross Diomedea exulans), the majority of blood Pb levels (95%) were below background exposure. Species was a significant factor (p = 0.0005) for mean blood Pb levels, which ranged from 3.62 (dark-mantled sooty albatross Phoebetria fusca) to 14.68 μg/dL (wandering albatross). Fewer individual blood Cd levels (less than 60%) were within background exposure levels. Species was not significant (p = 0.7145). The Pearson correlation coefficient between Pb and Cd was r = 0.3389 (p = 0.0262), and varied by species. Overall, the results suggest Pb and Cd are not a primary cause for concern in these seabirds. This work contributes to a multi-disciplinary ecological risk ...